Ultra-thin copper foil suitable for HDI board and preparation method and application thereof
By using specific additives and electrolytes in the preparation process of ultra-thin copper foil, combined with the surface treatment process, the rigidity of copper foil is improved, and the problem of poor rigidity performance of existing ultra-thin copper foil is solved, and the processing requirements of HDI boards are met.
Patent Information
- Application Number
- CN202310853218.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-07-12
AI Technical Summary
The existing ultra-thin copper foil has poor rigidity and cannot meet the processing requirements of high-density interconnect (HDI) boards.
By using specific additives and electrolytes in the preparation process of electrolytic copper foil, the crystallization process of the foil is controlled, and the surface treatment process such as coarseness and curing is combined to improve the rigidity of the copper foil.
The prepared ultra-thin copper foil has a high tensile strength and folding resistance, which can effectively solve the problem of poor rigidity of copper foil during HDI board processing.
Smart Images

Figure BDA0004335021790000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper foil manufacturing, and in particular relates to an ultra-thin copper foil suitable for an HDI board and a preparation method and application thereof. Background Art
[0002] With the development trend of consumer electronic products becoming thinner, more integrated and more multifunctional, the requirements for the signal transmission capability, wiring density and multi-layer of circuit boards are getting higher and higher. High-density interconnect (HDI) technology can provide higher-density circuit wiring, which can make the design of terminal products more miniaturized. HDI boards using micro-blind buried via technology have the characteristics of high-density integration, which can make the design of electronic products efficient, energy-saving, small and beautiful. Electronic products in many fields such as civilian consumer electronic products, industrial machines, servers, base stations, aerospace, etc. need to use HDI boards, and with the intelligent upgrading of electronic products and the increase in market demand, the development of HDI boards will be very rapid.
[0003] The processing of HDI boards is complex and requires multiple hot pressing and drilling. During the production process, the copper foil and the substrate need to withstand the physical and chemical effects of multiple hot pressing and drilling. Therefore, the electrolytic copper foil used for HDI boards is required to have moderate rigidity, good fatigue resistance, thermal stability and adhesion. However, in the prior art, the obtained electrolytic copper foil is usually low in rigidity and difficult to be applied to HDI boards that require multiple processing.
[0004] CN111910223A discloses an additive for electrolytic copper foil suitable for HDI board and a production process of electrolytic copper foil. The electrolytic copper foil suitable for HDI board is produced by using an additive containing brightener SPS, DPS and an aqueous solution of gelatin. The copper foil has a thickness of 12 to 105 μm, a stable profile peak, a uniform lattice size, a room temperature tensile strength of ≥400 MPa, a high temperature tensile strength of ≥200 MPa, a room temperature elongation of ≥10%, a high temperature elongation of ≥15%, a folding endurance of ≥3000 times, high airborne strength and good copper foil toughness, and solves the problem of copper foil breakage during the processing of HDI board.
[0005] Ultra thin copper foil is a copper foil for electronic circuits with a thickness of 12μm or less. In recent years, in order to meet the requirements of PCB manufacturing process and obtain higher density wiring, the demand for ultra thin copper foil has increased significantly. Although CN1160423283A, CN114921817A and CN116180165A disclose ultra thin electrolytic copper foil, the ultra thin copper foil has poor rigidity and cannot meet the processing requirements of HDI board. How to make ultra thin copper foil solve the rigidity problem in the processing of HDI board is a difficult problem in the current industry. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an ultra-thin copper foil suitable for HDI boards and a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing an ultra-thin copper foil suitable for an HDI board comprises the following steps: electrolyzing the foil using an additive and an electrolyte to obtain the ultra-thin copper foil.
[0009] Preferably, the electrolyte contains 90-95 g / L Cu 2+ , 130-150g / L H2SO4 and 15-25mg / L Cl - .
[0010] Further preferably, the flow rate of the electrolyte is 30-40m 3 / h.
[0011] Preferably, the flow rate of the additive is 30-40 mL / min.
[0012] Further preferably, the additive contains hexylbenzylamine salt (PPNI), sodium polydisulfide propane sulfonate (SPS), sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), hydrolyzed collagen and agarose.
[0013] More preferably, the additive contains hexylbenzylamine salt (PPNI) 0.2-0.5 g / L, sodium polydisulfide propane sulfonate (SPS) 2-3 g / L, sodium N,N-dimethyl-dithiocarbonyl propane sulfonate (DPS) 0.9-1.5 g / L, hydroxyethyl cellulose (HEC) 1.5-2.0 g / L, polyethylene glycol (PEG) 2.0-3.0 g / L, hydrolyzed collagen 0.4-0.8 g / L and agarose 3-4 g / L.
[0014] Most preferably, the additive contains 0.35 g / L hexylbenzylamine salt (PPNI), 2.5 g / L sodium polydisulfide propane sulfonate (SPS), 1.2 g / L sodium N,N-dimethyl-dithiocarbonyl propane sulfonate (DPS), 1.8 g / L hydroxyethyl cellulose (HEC), 2.5 g / L polyethylene glycol (PEG), 0.6 g / L hydrolyzed collagen and 3.5 g / L agarose.
[0015] The conditions for electrolytic foil making are: temperature 50-54°C, current density 50-85A / dm 2 .
[0016] The molecular weight of PEG in the present invention is 6000-10000Da; the molecular weight of hydrolyzed collagen is 2000-3000Da.
[0017] Preferably, the preparation method of the present invention further comprises surface treatment of the ultra-thin copper foil obtained by electrolysis.
[0018] Specifically, the surface treatment comprises the following steps:
[0019] (1) Pickling: The concentration of sulfuric acid during the pickling process is 130-150g / L and the temperature is 30-40°C;
[0020] (2) Coarsening: Cu 2+ The concentration of is 12-16 g / L, the concentration of sulfuric acid is 120-150 g / L, and the temperature of the system is 30-34 ° C;
[0021] (3) Curing: Cu 2+ The concentration of is 50-56g / L, the concentration of sulfuric acid is 90-120g / L, and the temperature of the system is 40-46°C;
[0022] (4) Water washing: Ultrapure water is used during the water washing process at a temperature of 25-35°C and the pH is washed to 6.8-7.2;
[0023] (5) Anti-oxidation treatment; Ni 2+ The concentration of Zn is 1.5-2.5g / L. 2+ The concentration is 3.5-4.5g / L, the K4P2O7 concentration is 70-100g / L, the pH value of the system is 10-11, and the temperature is 25-35℃;
[0024] (6) Water washing: Ultrapure water is used during the water washing process at a temperature of 25-35°C and the pH is washed to 6.8-7.2;
[0025] (7) Passivation: Cr 3+ The concentration of is 2.0-2.5g / L, the concentration of K4P2O7 is 70-100g / L, the pH of the system is 11-12, and the temperature is 25-35℃;
[0026] (8) Water washing: Ultrapure water is used during the water washing process at a temperature of 25-35°C and the pH is washed to 6.8-7.2;
[0027] (9) Silane spraying: The concentration of silane coupling agent is 1.0-1.5 g / L, the pH of the system is 9-12, and the temperature is 25-35°C;
[0028] (10) Drying: temperature 105-115°C.
[0029] Preferably, the roughening in step (2) is repeated at least once; and the curing in step (3) is repeated at least once.
[0030] The present invention also provides an ultra-thin copper foil prepared by the above preparation method. Preferably, the ultra-thin copper foil has a thickness of 8-12 μm, a folding endurance of ≥3000 times, and a peel strength of ≥1 N / mm.
[0031] The present invention also provides the use of the ultra-thin copper foil in preparing a high-density interconnection board (HDI board).
[0032] The present invention also provides a high-density interconnection board, which is processed from the above-mentioned ultra-thin copper foil.
[0033] The beneficial effects of the present invention are:
[0034] In the present invention, hexylbenzylamine salt (PPNI), sodium polydisulfide propane sulfonate (SPS), sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS) are brighteners, hydroxyethyl cellulose (HEC) and polyethylene glycol are moving agents, hydrolyzed collagen and agarose are leveling agents. Through the compounding of the brightener, the moving agent and the leveling agent, the crystallization process of the raw foil can be controlled, and the obtained raw foil has fine and uniform grains, uniform peak size and gentle peak shape, so that the raw foil has a certain rigidity fundamentally, and solves the problem of poor rigidity of ultra-thin copper foil in the processing of HDI plates.
[0035] At the same time, the present invention obtains copper nodules with small size, uniform distribution and firm bonding on the raw foil processing surface by matching the roughening and curing processes in the surface treatment process, so that the electrolytic copper foil processing surface has a small roughness and can still obtain a large peeling strength after bonding with the substrate; finally, the raw foil processing surface is further electroplated to deposit zinc, nickel and chromium metal layers, and a silane coupling agent is sprayed, so as to obtain higher high-temperature oxidation resistance and better bonding with the substrate. DETAILED DESCRIPTION
[0036] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0037] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.
[0038] When the embodiment gives a numerical range, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs.
[0039] The present invention does not limit the sources of the raw materials used. Unless otherwise specified, the raw materials used in the present invention are all common commercial products in the technical field. Unless otherwise specified, the solvents used in the solution of the present invention are all water, preferably ultrapure water. In the present invention, the molecular weight of PEG is 6000-10000Da, the molecular weight of hydrolyzed collagen is 2000-3000Da, and the silane coupling agent is KH-550.
[0040] Example 1
[0041] A method for preparing an ultra-thin copper foil suitable for an HDI board comprises the following steps:
[0042] S1. Electrolysis: adding electrolyte and additives into the electrolytic cell for electrolysis to produce ultra-thin copper foil;
[0043] The electrolysis conditions are: current density is 65A / m 2 , the electrolysis temperature is 52℃, and the electrolyte flow rate is 35m 3 / h, the additive flow rate is 32mL / min;
[0044] The electrolyte contains 92g / L Cu 2+ , 140g / L H2SO4 and 20mg / L Cl - .
[0045] The additive contains 0.35 g / L of hexylbenzylamine salt (PPNI), 2.5 g / L of sodium polydisulfide propane sulfonate (SPS), 1.2 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), 1.8 g / L of hydroxyethyl cellulose (HEC), 2.5 g / L of polyethylene glycol (PEG), 0.6 g / L of hydrolyzed collagen and 3.5 g / L of agarose.
[0046] S2, surface treatment: The ultra-thin copper foil obtained in step S1 is subjected to surface treatment, specifically, comprising the following steps:
[0047] (1) Pickling: The concentration of sulfuric acid during the pickling process is 140 g / L and the temperature is 35 °C;
[0048] (2) Coarsening: Cu 2+ The concentration of is 14 g / L, the concentration of sulfuric acid is 135 g / L, and the temperature of the system is 32°C;
[0049] (3) Curing: Cu 2+ The concentration of is 53 g / L, the concentration of sulfuric acid is 105 g / L, and the temperature of the system is 43 °C;
[0050] (4) Water washing: Ultrapure water was used during the water washing process at a temperature of 30°C until the pH value reached 7;
[0051] (5) Anti-oxidation treatment; Ni 2+ The concentration is 2.0g / L, Zn 2+ The concentration is 4.0 g / L, the K4P2O7 concentration is 85 g / L, the pH value of the system is 10, and the temperature is 30°C;
[0052] (6) Water washing: Ultrapure water was used during the water washing process at a temperature of 30°C until the pH value reached 7;
[0053] (7) Passivation: Cr 3+ The concentration of is 2.3g / L, the concentration of K4P2O7 is 85g / L, the pH of the system is 11, and the temperature is 30℃;
[0054] (8) Water washing: Ultrapure water was used during the water washing process at a temperature of 30°C until the pH value reached 7;
[0055] (9) Silane spraying: the concentration of the silicone coupling agent is 1.2 g / L, the pH of the system is 10, and the temperature is 30 °C;
[0056] (10) Drying: temperature 105-115°C.
[0057] Example 2
[0058] A method for preparing an ultra-thin copper foil suitable for an HDI board comprises the following steps:
[0059] S1. Electrolysis: adding electrolyte and additives into the electrolytic cell for electrolysis to produce ultra-thin copper foil;
[0060] The electrolysis conditions are: current density 50A / m 2 , the electrolysis temperature is 54°C, and the electrolyte flow rate is 30m 3 / h, the additive flow rate is 40mL / min;
[0061] The electrolyte contains 90g / L Cu 2+ , 130g / L H2SO4 and 15mg / L Cl - .
[0062] The additive contains 0.2 g / L of hexylbenzylamine salt (PPNI), 2.0 g / L of sodium polydisulfide propane sulfonate (SPS), 0.9 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), 2.0 g / L of hydroxyethyl cellulose (HEC), 3.0 g / L of polyethylene glycol (PEG), 0.4 g / L of hydrolyzed collagen and 3.0 g / L of agarose.
[0063] S2, surface treatment: The ultra-thin copper foil obtained in step S1 is subjected to surface treatment, specifically, comprising the following steps:
[0064] (1) Pickling: The concentration of sulfuric acid during the pickling process is 130 g / L and the temperature is 30 °C;
[0065] (2) Coarsening: Cu 2+ The concentration of is 12 g / L, the concentration of sulfuric acid is 120 g / L, and the temperature of the system is 34°C;
[0066] (3) Curing: Cu 2+ The concentration of is 50g / L, the concentration of sulfuric acid is 90g / L, and the temperature of the system is 46°C;
[0067] (4) Water washing: Ultrapure water was used during the water washing process at a temperature of 25°C until the pH value reached 7.2;
[0068] (5) Anti-oxidation treatment; Ni 2+ The concentration of Zn is 1.5g / L. 2+ The concentration is 3.5 g / L, the K4P2O7 concentration is 70 g / L, the pH value of the system is 11, and the temperature is 35°C;
[0069] (6) Water washing: Ultrapure water was used during the water washing process at a temperature of 25°C until the pH value reached 7.2;
[0070] (7) Passivation: Cr 3+ The concentration of is 2.0g / L, the concentration of K4P2O7 is 70g / L, the pH of the system is 12, and the temperature is 35℃;
[0071] (8) Water washing: Ultrapure water was used during the water washing process at a temperature of 25°C until the pH value reached 7.2;
[0072] (9) Silane spraying: the concentration of the silicone coupling agent is 1.5 g / L, the pH of the system is 9, and the temperature is 25 °C;
[0073] (10) Drying: temperature 105-115°C.
[0074] Example 3
[0075] A method for preparing an ultra-thin copper foil suitable for an HDI board comprises the following steps:
[0076] S1. Electrolysis: adding electrolyte and additives into the electrolytic cell for electrolysis to produce ultra-thin copper foil;
[0077] The electrolysis conditions are: current density is 85A / m 2 , the electrolysis temperature is 50℃, and the electrolyte flow rate is 40m 3 / h, the additive flow rate is 30mL / min;
[0078] The electrolyte contains 95g / L Cu 2+ , 150g / L H2SO4 and 25mg / L Cl - .
[0079] The additive contains 0.5 g / L of hexylbenzylamine salt (PPNI), 3.0 g / L of sodium polydisulfide propane sulfonate (SPS), 1.5 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), 1.5 g / L of hydroxyethyl cellulose (HEC), 2.0 g / L of polyethylene glycol (PEG), 0.8 g / L of hydrolyzed collagen and 4.0 g / L of agarose.
[0080] S2, surface treatment: The ultra-thin copper foil obtained in step S1 is subjected to surface treatment, specifically, comprising the following steps:
[0081] (1) Pickling: The concentration of sulfuric acid during the pickling process is 150g / L and the temperature is 40°C;
[0082] (2) Coarsening: Cu 2+ The concentration of is 16 g / L, the concentration of sulfuric acid is 150 g / L, and the temperature of the system is 30°C;
[0083] (3) Curing: Cu 2+ The concentration of is 56 g / L, the concentration of sulfuric acid is 120 g / L, and the temperature of the system is 40°C;
[0084] (4) Water washing: Ultrapure water was used during the water washing process at a temperature of 35°C until the pH value reached 6.8;
[0085] (5) Anti-oxidation treatment; Ni 2+ The concentration is 2.5g / L, Zn 2+ The concentration is 4.5 g / L, the K4P2O7 concentration is 100 g / L, the pH value of the system is 11, and the temperature is 25°C;
[0086] (6) Water washing: Ultrapure water was used during the water washing process at a temperature of 35°C until the pH value reached 6.8;
[0087] (7) Passivation: Cr 3+ The concentration of is 2.5g / L, the concentration of K4P2O7 is 100g / L, the pH of the system is 11, and the temperature is 25℃;
[0088] (8) Water washing: Ultrapure water was used during the water washing process at a temperature of 35°C until the pH value reached 6.8;
[0089] (9) Silane spraying: the concentration of the silicone coupling agent is 1.0 g / L, the pH of the system is 12, and the temperature is 35 °C;
[0090] (10) Drying: temperature 105-115°C.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 1 is that the additives are different, specifically, 3-mercaptopropane sulfonic acid (MPS) is used instead of hexylbenzylamine salt (PPNI).
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 1 is that the amount of sodium polydisulfide propane sulfonate (SPS) and sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS) in the additive is different. Specifically:
[0095] The additive contains 0.35 g / L of hexylbenzylamine salt (PPNI), 1.5 g / L of sodium polydisulfide propane sulfonate (SPS), 1.5 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), 1.8 g / L of hydroxyethyl cellulose (HEC), 2.5 g / L of polyethylene glycol (PEG), 0.6 g / L of hydrolyzed collagen and 3.5 g / L of agarose.
[0096] Comparative Example 3
[0097] The difference between this comparative example and Example 1 is that the amounts of hexylbenzylamine salt (PPNI), sodium polydisulfide propane sulfonate (SPS) and sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS) in the additives are different. Specifically:
[0098] The additive contains 1.0 g / L of hexylbenzylamine salt (PPNI), 1.2 g / L of sodium polydisulfide propane sulfonate (SPS), 2.5 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate (DPS), 1.8 g / L of hydroxyethyl cellulose (HEC), 2.5 g / L of polyethylene glycol (PEG), 0.6 g / L of hydrolyzed collagen and 3.5 g / L of agarose.
[0099] The performance test results of the ultra-thin copper foil after surface treatment of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1, wherein, rigidity test: the ultra-thin copper foil is cut into samples with a length of 100 mm×20 mm, and an MIT bending test is performed until the copper foil breaks, wherein the bending radius is 0.5 mm, the load is 500 g, and the bending angle is ±135°. The number of times the sample breaks is examined, and the greater the number of times the sample breaks, the better the rigidity of the ultra-thin copper foil.
[0100] Table 1 Properties of ultra-thin copper foil after surface treatment
[0101]
[0102] It can be seen from Examples 1-3 in the above table that the ultra-thin copper foil produced by the preparation method of the ultra-thin copper foil suitable for HDI board of the present invention has a thickness of 8-12 μm, and in terms of structure: fine and uniform crystallization, stable profile peak value, and consistent size of copper nodules; in terms of performance: tensile strength at room temperature ≥350 MPa, elongation at room temperature is 6.3%-8.0%, tensile strength at high temperature ≥300 MPa, elongation at high temperature is 10.3%-11.6%, roughness of treated surface Rz≤2.0 μm, peel strength ≥1.0 N / mm, and folding endurance ≥3000 times, which can effectively solve the problem of poor rigidity of copper foil in the processing of HDI board.
[0103] At the same time, it can be seen from comparative examples 1-3 that when the type or amount of the additive component is changed, the rigidity of the produced ultra-thin copper foil is greatly affected, and its folding times are less than 3000, and the rigidity is poor. This shows that not all conventional additives can solve the problem of poor rigidity of copper foil in the HDI sheet processing process.
[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an ultra-thin copper foil suitable for HDI boards, characterized in that: The following steps are involved: Using additives and electrolyte to electrolyze foil to obtain the ultra-thin copper foil; The additive contains 0.2-0.5 g / L of hexylbenzylamine salt, 2-3 g / L of sodium polydisulfide propane sulfonate, 0.9-1.5 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate, 1.5-2.0 g / L of hydroxyethyl cellulose, 2.0-3.0 g / L of polyethylene glycol, 0.4-0.8 g / L of hydrolyzed collagen and 3-4 g / L of agarose; The electrolyte contains 90-95g / L Cu 2+ , 130-150g / L H2SO4 and 15-25mg / L Cl - .
2. The preparation method according to claim 1, characterized in that: The flow rate of the electrolyte is 30-40m 3 / h; the flow rate of the additive is 30-40mL / min.
3. The preparation method according to claim 1, characterized in that: The additive contains 0.35 g / L of hexylbenzylamine salt, 2.5 g / L of sodium polydisulfide propane sulfonate, 1.2 g / L of sodium N,N-dimethyl-disulfide carbonyl propane sulfonate, 1.8 g / L of hydroxyethyl cellulose, 2.5 g / L of polyethylene glycol, 0.6 g / L of hydrolyzed collagen and 3.5 g / L of agarose.
4. The preparation method according to claim 1, characterized in that: The conditions for electrolytic foil making are: temperature 50-54°C, current density 50-85A / dm 2 .
5. The preparation method according to claim 1, characterized in that: The method also includes surface treatment of the ultra-thin copper foil obtained by electrolysis.
6. The ultra-thin copper foil prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The thickness of the ultra-thin copper foil is 8-12 μm.
7. Use of the ultra-thin copper foil according to claim 6 in preparing a high-density interconnection board.
8. A high density interconnection board, characterized in that: The ultra-thin copper foil is processed from the ultra-thin copper foil according to claim 6.
Citation Information
Patent Citations
Additive for electrolytic copper foil suitable for HDI plate and electrolytic copper foil production process
CN111910223A
Ultrathin electrolytic copper foil and preparation method and application thereof
CN114921817A
High-performance ultra-thin electronic copper foil as well as preparation method and application thereof
CN116180165A
Production process of double-light copper foil for lithium battery
CN115198321A